Ethnomathematics for the strengthening of basic operations in piapocos indigenous children. - Rodríguez, Angye Fernanda; Saiz Sáenz, Martha Leonor (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article presents the challenges faced by indigenous students belonging to the Piapoco ethnic group in the department of Guainía, in the development of mathematical thinking, specifically in basic mathematical operations. Addressing this issue, to improve these abilities in students, through Ethnomathematics and the approach of Realistic Mathematics Education (RME), where the objective was the design of a didactic sequence with the implementation of the qualitative approach, of ethnographic type, with the technique of ethnomathematics, where they were approached with the different analyzes and the coexistence with the environment and the context that the researcher has had. Based on the data presented, on the information collected and the stories told by the grandparents and indigenous Piapoco scholars, the great need to generate activities through a didactic sequence that was contextualized to their environment, reality and traditions was evident; because they, in their worldview, traditions and culture, are immersed in basic operations during their daily activities, however, it is essential to enhance these processes from reality.